Reliability and Physiological Interpretation of Pulmonary Gas Exchange by “Circulatory Equivalents” in Chronic Heart Failure - Chunting Tan; Harry B. Rossiter; Janos Porszasz; T. Scott Bowen; Klaus K. Witte; William W. Stringer; Richard Casaburi; James E. Hansen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundPeak ratios of pulmonary gas‐exchange to ventilation during exercise (V˙O2/V˙E and V˙CO2/V˙E, termed “circulatory equivalents”) are sensitive to heart failure (HF) severity, likely reflecting low and/or poorly distributed pulmonary perfusion. We tested whether peak V˙O2/V˙E and V˙CO2/V˙E would: (1) distinguish HF patients from controls; (2) be independent of incremental exercise protocol; and (3) correlate with lactate threshold (LT) and ventilatory compensation point (VCP), respectively. Methods and ResultsTwenty‐four HF patients (61±11 years) with reduced ejection fraction (31±8%) and 11 controls (63±7 years) performed ramp‐incremental cycle ergometry. Eighteen HF patients also performed slow (5±1 W/min), medium (9±4 W/min), and fast (19±6 W/min) ramps. Peak V˙O2/V˙E and V˙CO2/V˙E from X‐Y plot, and LT and VCP from 9‐panel plot, were determined by 2 independent, blinded, assessors. Peak V˙O2/V˙E (31.2±4.4 versus 41.8±4.8 mL/L; P<0.0001) and V˙CO2/V˙E (29.3±3.0 versus 36.9±4.0 mL/L; P<0.0001) were lower in HF than controls. Within individuals, there was no difference across 3 ramp rates in peak V˙O2/V˙E (P=0.62) or V˙CO2/V˙E (P=0.97). Coefficient of variation (CV) in peak V˙O2/V˙E was lower than for LT (5.1±2.1% versus 8.2±3.7%; P=0.014), and coefficient of variation in peak V˙CO2/V˙E was lower than for VCP (3.3±1.8% versus 8.7±4.2%; P<0.001). In all participants, peak V˙O2/V˙E was correlated with, but occurred earlier than, LT (r2=0.94; mean bias, −0.11 L/min), and peak V˙CO2/V˙E was correlated with, but occurred earlier than, VCP (r2=0.98; mean bias −0.08 L/min). ConclusionsPeak circulatory equivalents during exercise are strongly associated with (but not identical to) LT and VCP. Peak circulatory equivalents are reliable, objective, effort‐independent indices of gas‐exchange abnormality in HF.